The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1055/s-0040-1702217
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Haemophilus influenzae Type B, Diphtheria, and Tetanus in Children from Major Cities of Pakistan: A Community-Based Study

Abstract: Objective Pentavalent vaccine has been introduced in Pakistan against tetanus, diphtheria, Haemophilus influenzae type B (HiB), pertussis, and hepatitis B virus. Methods This study was designed to determine protection against diphtheria, tetanus, and HiB in children of age 18 to 24 months from community which had received all three doses of pentavalent vaccine. Results Overall, 97% were having immunity against HiB, 97% against tetanus, and 88% against diphtheria. Our study showed that child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Controversially to previous reports, our results suggested that association among FM, FFM, F %, and ALP is not sufficient. Similar to our findings, a study revealed no direct relation of vitamin D deficiency with ALP (15), and another study also pointed out Vitamin D concentrations were not related to ALP in drug-naïve individuals without liver disease (25). Besides, there was also no significant cross-sectional association between 25(OH)D and bone turnover markers (26).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Controversially to previous reports, our results suggested that association among FM, FFM, F %, and ALP is not sufficient. Similar to our findings, a study revealed no direct relation of vitamin D deficiency with ALP (15), and another study also pointed out Vitamin D concentrations were not related to ALP in drug-naïve individuals without liver disease (25). Besides, there was also no significant cross-sectional association between 25(OH)D and bone turnover markers (26).…”
Section: Discussionsupporting
confidence: 88%
“…A metaanalytic study revealed a correlation between obesity and vitamin D deficiency is stronger in the Asian population than in the European-American population. Furthermore, it is also related to skin color, clothing style, regional differences (14)(15)(16). A Turkish study showed that vitamin D levels were low in 66.6% of women of reproductive age in Istanbul (17) and it was 93% in the entire female population (18).…”
Section: Discussionmentioning
confidence: 99%